Exo Olo Task Learning Model with Case method To Improve Students' HOTS on the Distribution of Flora and Fauna - Andika Rahman; Nofrion Nofrion; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2022)
The purpose of writing this article is to explain the influence of the application of the Exo Olo Task learning model with the Case method (CM) to Improve students' high-level thinking skills on the material distribution of flora and fauna in Indonesia and the world. Where the Exo Olo Task Learning Model with Case method is in line with the 2013 curriculum which applies student-centered learning. The distribution of Flora and Fauna in Indonesia and the World studied by students in high school class XI is included in the scope of physical geography. The research method in this study is a literature study with sources from various articles through searches on the internet and supported by related books. This writing obtained the results that the Exo Olo Task Learning Model with the Case method can improve students' high-level thinking skills. So, the Exo Olo Task Learning Model Method with the Case method can be applied in geography learning in high school. The role of the teacher is needed in the implementation of the Exo Olo Task Learning Model with the Case method as a facilitator of student learning.